2022
DOI: 10.1037/tep0000382
|View full text |Cite
|
Sign up to set email alerts
|

Racial and ethnic diversity among clinical psychology doctoral students applying for internship.

Abstract: Racial and ethnic diversity constriction in the psychology training-to-workforce pipeline has been broadly identified at the undergraduate, graduate, and licensure levels. Within that context, the present study sought to investigate the rate at which racial and ethnic minority students matched for internship compared to majority non-Hispanic White graduate students. Consistent with prior reports, racial and ethnic minority students were significantly underrepresented in clinical psychology doctoral programs. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 42 publications
(64 reference statements)
0
14
0
Order By: Relevance
“…One potential approach to addressing these issues is to combine data from different studies to increase the number of available participants from underrepresented groups (e.g., Dimmick & Callahan, 2022) if the same variables of interest are available in all different waves or data collection or data sets, although there are also potential limitations in this approach, particularly cohort effects. Thus, researchers using these methods should statistically test and control for cohort effects when possible.…”
Section: Potential Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…One potential approach to addressing these issues is to combine data from different studies to increase the number of available participants from underrepresented groups (e.g., Dimmick & Callahan, 2022) if the same variables of interest are available in all different waves or data collection or data sets, although there are also potential limitations in this approach, particularly cohort effects. Thus, researchers using these methods should statistically test and control for cohort effects when possible.…”
Section: Potential Solutionsmentioning
confidence: 99%
“…There is a need for empirical research about professional psychology trainees and their experiences throughout the training process (Callahan & Watkins, 2018a, 2018b, 2018c. The data obtained in such studies can help answer questions about important topics such as admission and attrition patterns (Callahan et al, 2018), differential internship match rates (Callahan et al, 2010(Callahan et al, , 2014Dimmick & Callahan, 2022;Lund, 2021;Parent & Williamson, 2010), representation of different marginalized groups in psychology training (Andrews & Lund, 2015;Callahan et al, 2018), experiences of students participating in the predoctoral internship match (Lund, 2021;Parent et al, 2016), and student publication productivity (Lund, Bouchard, & Thomas, 2016). This research is especially critical for addressing issues related to diversity, equity, and inclusion (DEI) in professional psychology education and training (Callahan et al, 2018), including as it relates to disability and its intersection with other marginalized identities (Lund et al, 2023).…”
mentioning
confidence: 99%
“…The sample size is limited to the location specific to Northeastern United States and only includes APA-accredited programs and does not fully represent doctoral psychology programs across the United States nor programs that are not APA-accredited. Although the demographics are representative of the larger population of psychology doctoral students across the United States (Dimmick & Callahan, 2021;Santana & Fouad, 2017), this sample is limited because it was not adequately powered to assess the study variables in underrepresented populations in graduate school. This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Limitationsmentioning
confidence: 99%
“…We found that SRRers were more likely to be members of minoritized sexual orientation and/or racial/ethnic groups, and to have a history of mental health difficulties. When considering that psychology has continued to struggle to gain adequate representation of these marginalized backgrounds in research (Callahan et al, 2018;Dimmick & Callahan, 2021;Miller & Orsillo, 2020), it becomes crucial that psychologists not also discriminate against someone for their personal motivations to pursue research. Along these lines, while this study has primarily discussed SRR on mental illness, we hope our arguments are also considered in the context of SRR on non-metal health topics and intersectionality (e.g., people with multiple disadvantaged identities), including scholars who use their experiences with their identities as motivation to pursue their respective topics (e.g., an African American/Black researcher studying health disparities among African American/black samples; Harris, 2021).…”
Section: Accepting Srrers Connects To Diversity and Inclusion Efforts In Psychologicalmentioning
confidence: 99%